The Brain eating amoeba Naegleria fowleri and Primary Amoebic Meningoencephalitis in a warming world: An overlooked Consequence of Climate Change - Robinson, Jared; Banerjee, Indrajit; Banerjee, Indraneel (Journal of Advances in Internal Medicine, 2025)
The choice of “fresh” water bodies for a cooling swim on a hot summer afternoon result in a life-threatening infection caused by a brain eating amoeba known as Naegleria fowleri. Reports of infections caused by this amoeba have recently surfaced reports from both in the United States of America, Australia and India. Naegleria fowleri is a eukaryotic free-living amoeba, which belongs to the Percolozoa phylum. This amoeba has 3 stages in its life cycle namely: a cystic from, a trophozoite form and a flagellate form. The trophozoite being the infectious stage. N. fowleri is typically found throughout our environment from bodies of fresh water to soil. The Ameoba is neurotropic and tracks along the nasal mucosa and via the olfactory nerve through the cribriform plate (which is not completely fused in the younger populous) to ultimately infect the olfactory bulbs and the brain, thus causing (primary amoebic meningoencephalitis) abbreviated as PAM. The treatment of PAM is both supportive and specific. A simple and trivial but proven method to prevent the infection is simply keeping one’s head above water when in such open bodies of fresh water. The adequate chlorination of public recreational swimming pools and bodies of water is empirical to aid in the control of the infection. Naegleria fowleri is a rare but deadly infection and the lack of an effective treatment and the associated high mortality rate can only thus be countered by increasing the publics knowledge and awareness surrounding the disease. Countries such as India are making remarkable breakthroughs with lower mortality rates, due to vigorous and intense surveillance, testing and aggressive treatment strategies. India’s success in controlling the outbreak should be used as the yardstick for other countries to follow on an international basis when trying to control this infectious Amoeba.